Global Scaling up Hand Washing Project : Endline Assessment of the Enabling Environment in Peru - Favin, Michael (World Bank, Washington, DC, 2014)
The Water and Sanitation Program (WSP) is in the final phase of the Global Scaling up Hand washing Project, implemented in Peru, Senegal, Tanzania, and Vietnam. In Peru, where the project is known as Iniciativa de Lavado de Manos, or the Hand washing Initiative (HWI), the specific target is to reach 5.1 million women and children under the age of 12 with hand washing messages by the end of the four-year implementation period (November 2010). The ultimate goal is to have 1.3 million people practicing improved hand washing behaviors. This report summarizes the end line assessment of the enabling environment (EE) for the Global Scaling up Hand washing Project in Peru. This assessment aimed to evaluate the robustness of the programmatic conditions for scale up and sustainability as the project's implementation phase was winding down. Research carried out from October 18 to November 5, 2010, followed a 2007 baseline EE assessment. The same instrument was used in both assessments, with some modifications and additions made in 2010 based on program experience and learning. An international consultant carried out the assessment.